Experimental deermination of torque converter parameters in conditions of low-power drive motor - Соловьев, Владимир Михайлович (Eastern-European Journal of Enterprise Technologies, 2013)
The paper is devoted to the issue of conducting experimental studies of torque converters for accurate determination of their external and internal parameters of operating in conditions of low-power drive motor by selecting the optimal gear ratio and rotational speed of the impeller n1. On the basis of the graphical optimization method the algorithm was developed based on imposing the constraints for the maximum motor power, the minimum Reynolds number and the resonance speed of impeller rotation. The theoretical issue of experimental studies of the torque converter in the area of quadratic losses of the VTI graph is resolved. The graph for the coefficient of hydraulic friction losses depending on several flow sections and the Reynolds number is shown. The diagram of dependence of the coefficient of hydraulic friction losses for several flow sections on the gear ratio λmn=f (i) is presented.